Pengayaan Yodium dan Kadar NaCl pada Garam Krosok menjadi Garam Konsumsi standar SNI Enrichment of Iodium and Sodium Cloride in the Traditional Salt become Consumtion Salt INS Standard - M. Nur; I. Marhaendrajaya; Sugito Sugito; T. Windarti; Arnelli Arnelli; R. Hastuti; A. Haris; W. H. Rahmanto; Didik Setiyo Widodo; F. Ariyanto; Z. Muhlisin; J. E. Suseno; E. Setiawati; H. Sutanto; Priyono Priyono; M. Izzati; R. Hariyati; S. Tana; B. Raharjo; D. Ispriyanti; Farikhin Farikhin; A. Rusgiyono; Suhartono Suhartono (JURNAL SAINS DAN MATEMATIKA, 2015)
This research has been carried out in the quality improvement of traditional salt (krosok salt) into salt consumption for the Indonesian National Standard. This report is devoted to the elevated levels of NaCl and KIO3. Increased levels of NaCl and Iodine (represented by KIO3) is done by washing the salt with the traditional clothes washer with two rounds and by using water with saline solution at 22-24 Be (known as the old water). Traditional salt taken from three districts, such as Pati District, Jepara District, and Rembang District. We found that the concentration of NaCl in the treatment salt maximum is 96 % and Iodium or present of KIO3 is 40 ppm. Key words: Salt, traditional, INS, Consumtion, NaCl, KIO3